Association between Drinking Water Treatment and Diarrhea Among Under-Five Years Children - Yesvi Zulfiana; Nurul Fatmawati; Siskha Maya Herlina (Journal for Quality in Public Health, 2021)
Diarrhea is still a health problem in the world, especially in developing countries. The World Health Organization (WHO) explained that the cause of death in infants and toddlers is diarrhea, which ranks second. Meanwhile, based on Indonesia's health profile in 2015, there were 18 outbreaks of diarrhea in 11 provinces, 18 districts / cities, with 1,213 sufferers and 30 deaths (CFR 2.47%). Several factors related to the incidence of diarrhea are maternal care, birth weight and environmental sanitation. This study aims to determine the relationship between maternal parenting, birth weight and environmental sanitation with the incidence of diarrhea in children under five in Selagalas Village, the working area of ​​Cakranegara Health Center. This study used a cross-sectional quantitative design on 104 toddlers who were selected by systematic random sampling in three selected environments in Selagalas Village. Data were collected by structured interviews using questionnaires and observation sheets. Data analysis was carried out bivariately using logistic regression to see the relationship between family drinking water management and the incidence of diarrhea. 64.42% of children under five were found to have experienced diarrhea. The variable related to the incidence of diarrhea was the lack of drinking water management with a value of P = 0.03. The management of family drinking water is still lacking so it is necessary to make health promotion efforts for the family to improve the management of family drinking water that meets the requirements so that it can improve the behavior of a clean and healthy life.